Fine needle aspiration cytology in the diagnosis of uncommon types of lymphoma. Issue 11 (4th November 2003) - Mayall, F; Darlington, A; Harrison, B
Abstract : Aims: Fine needle aspiration (FNA) cytology is an accepted means of diagnosing and typing common forms of lymphoma, particularly small lymphocytic lymphoma, follicular lymphoma, and large B cell lymphoma. However, its usefulness for diagnosing less common forms of lymphoma is not clearly established and this study was designed to examine this. Methods: The study reviewed the FNAs of suspected lymphomas collected over a period of approximately five years. Results: FNA samples were available for 138 definite lymphomas; most were common forms of B cell lymphoma. However, there was also one Burkitt lymphoma (BL), two Burkitt-like large B cell lymphomas, 15 classic Hodgkin lymphomas (HLs), two nodular lymphocyte predominant Hodgkin lymphomas, four mantle cell lymphomas, two mediastinal (thymic) large B cell lymphomas (MLBCLs), 11 peripheral T cell lymphomas (PTCLs), and five T cell rich large B cell lymphomas (TCRLBCLs). Conclusions: FNA diagnosis of BL was possible with immunoflow cytometry (IFC), cell block immunohistochemistry (IHC), and cell block fluorescent in situ hybridisation for c-myc alteration. It was difficult to make a definite diagnosis of HL and MLBCL on FNA alone. Both tend to be sclerotic tumours and FNA tends to yield scanty neoplastic cells. The FNA diagnosis of PTCL depended on cell block IHC; IFC was not usually useful. TCRLBCL did not show light chain restriction on IFC of FNA samples, probably because of frequent reactive B cells in the tumour. Thus, HL, MLBCL, and TCRLBCL are often difficult to diagnose accurately on FNA cytology, even when using IFC and cell block IHC.